(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
In this study, number of face masks were prepared with two different base materials ; polyvinyl alcohol( PVA) polymer and gelatin polymer masks as a base materials .Arabic gum and activated charcoal were used seperatly by (0.2 ,0.4 ,0.6 and,0.8) wt % to enhance the skincare and removing blackheads. The physical properties like spread ability, drying time, irritation test, homogeneity test and PH test evaluated .Results showed that The prepared samples have good spread ability ( 3-7) cm therefore the polyvinyl and gelatin based mask distribute evenly on the skin, and perfect drying time and with no redness and without inflammation and no swelling in the skin. The mask is suitable for all kinds of skin due to its natural components and odorless which whitening the skin and make it soft, clean and shine. Gelatin based mask suitable to remove black heads because it have good adhesion with the skin. polyvinyl based mask removed easily more than gelatin based mask due less adhesion to skin than gelatin mask.